Dye laser micro-fluidic amplifiers - Russell-Hill, Paula (Trinity College (Dublin, Ireland). School of Physics, 2011)
Dye lasers, based on micro-fluidic systems, have been the focus of increasing attention in recent years. Whereas micro-fluidics networks, such as a 'lab-on-a-chip', involve expensive and complicated fabrication processes, the use of micro-capillaries as cavities for dye solutions provides a low cost option. Employing the well-known organic laser dye, Rhodamine 590, as the active material, a series of micro-amplifiers are developed by incorporating the dye solutions into various micro-cavities, namely, capillary tubes and photonic crystal fibres (PCFs), via capillarity.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.